INCREASING STUDENTS’ INTEREST IN LEARNING ENGLISH - Nodira Toirova Yusupovna (Ustozlar uchun, 2025)
Abstract:This article discusses methods for increasing students’ interest during English lessons. It highlights effective ways to engage students in language learning through interactive methods, games, group activities, and modern technologies.